PENERAPAN PRINSIP PASSIVE COOLING PADA UMKM SHOPPING CENTER DI PEKANBARU - Muhammad Agramansyah Hasyim; Yohannes Firzal; Mira Dharma Susilawaty (Jurnal Arsitektur ARCADE, 2020)
Abstract: UMKM shopping center is a facility that supports the fulfillment of UMKM development needs in Pekanbaru City. Where the City of Pekanbaru is part of the State of Indonesia which has begun the era of the MEA with the start of creative partnerships. Then the required facilities that can be requested and the quality improvement container needed, especially in the city of Pekanbaru. Pekanbaru City as the capital of Riau Province, has relatively high economic growth in UMKM. Based on data from the UMKM DISKOP in 2015 there were 535,139 activists. That shows the benefits in economic growth. But it is not balanced with support and supporting facilities. The application of passive cooling is applied as a method in controlling thermal in buildings, with the aim of providing comfort. With the concept of air movement which means moving, the implementation of passive cooling that relies on wind movement in optimizing thermal regulation of activities that involve the movement of visitors inside the building.Keyword: Pekanbaru,, UMKM, Shopping center, Passive cooling, thermal.Abstrak: UMKM shopping center adalah fasilitas yang berupaya memenuhi kebutuhan pengembangan UMKM di Kota Pekanbaru. Dimana Kota Pekanbaru yaitu bagian dari Negara Indonesia telah memasuki era MEA dengan dimulainya perekonomian kreatif. Maka dibutuhkan fasilitas yang dapat mempromosikan dan wadah peningkatan kualitas produk yang dibutuhkan, terutama di kota Pekanbaru. Kota Pekanbaru sebagai ibu kota Provinsi Riau, memiliki pertumbuhan ekonomi tergolong tinggi terutama di UMKM. Berdasarkan data DISKOP UMKM pada 2015 terdapat 535.139 penggiat. Itu menunjukkan keuntungan dalam pertumbuhan ekonomi. Namun  tidak diimbangi dengan ketersediaan dan fasilitas pendukung. Penerapan passive cooling yang diterapkan sebagai metode dalam mengendalikan termal pada bangunan, dengan tujuan memberikan kenyamanan. Dengan konsep air movement yang berarti bergerak, implementasi dari passive cooling yang mengandalkan pergerakan angin membrikan  kenyaman dalam pengoptimalam pengaturan termal terhadap aktivitas berupa pergerakan pengunjung yang berada di dalam bangunan.Kata Kunci: Pekanbaru, UMKM, Shopping Center, Passive cooling, termal.